Meta-analysis of the Effect of Jigsaw Model Based on Hybrid-Based Learning on Students' Critical Thinking Skills - Wiwid Suryono; Linda Winiasri; Nofirman Nofirman; Mardiati Mardiati; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to determine the effect of the jigsaw learning model based on hybrid learning on students' critical thinking skills. This type of research is quantitative research with a meta-analysis approach. Data sources come from analyzing national and international journals. Inclusion criteria are research must come from Scopus and SINTA-indexed journals or proceedings; Data source searches come from Google Scholar, ERIC, IEEE, and Wiley; Research must have experimental and control classes; Research must be published from 2017-2023; Research has a relationship with research variables and research has a value (t), (r) and (f). Data analysis is quantitative statistical analysis with the help of the JSAP application. The results of this study concluded that the average value of the summary effect size or mean effect size of the entire study (ES = 0.896; p < 0.001) with very high criteria. This finding explains that the jigsaw learning model based on hybridized learning has a great influence on students' critical thinking skills.